Distance and Suffering: Humanitarian Discourse in the Age of Mediatization - Anne Vestergaard (Copenhagen Business School (CBS), 2011)
This thesis explores the history of humanitarian organizations as agents in public life. When taking on the role as mediators between Western publics and distant sufferers, what conception of social responsibility do humanitarian organizations promote? What are the consequences of the institutional context of these organizations on the form of social responsibility that they are able to promote? In a historical perspective, what changes in these conceptualizations can we observe and to what extent can we understand them as resulting from institutional changes? These questions are asked with the assumption that the discourse of humanitarian organizations is at once a reflection of and a force in the configuration of dispositions in target publics. Enquiring about the history of humanitarian organizations as agents in public life, thus, means enquiring about the ways in which over the past 40 years, these organizations have given meaning to our relation to different sufferers and contributed to shaping our individual and collective conception of the scope and nature of our social responsibility....
hdl:10398/8318
Keywords: 650